Identification and Seedlings Growth Evaluation of Shorea Species-Producing Tengkawang - Windyarini, Eritrina; Hasnah, Tri Maria (Balai Penelitian Kehutanan Manado, 2015)
Most ofÂ non timber forest product (NTFP) utilization taken from natural forests which decrease on productivity annually, including tengkawang producer species which taken from West Kalimantan natural forests. This condition needs an effort to preserve those species from natural population utilization through plantation forest development that require spesific strategy. This study was part of breeding strategy of shorea species producing tengkawang which aimed to species identify and seedling growth evaluation used genetic material from 2 (two) population from West Kalimantan. The research was arranged in 2 (two) steps, i.e.1) species identification used morphology characteristic difference, and 2) seedling growth evaluation (height,diameter,sturdiness). Seedling growth evaluation was arranged in RCBD, with 5 plot (combination of species and source population), contained 25 seedlings and 4 replications (blocks). The result showed that seedlings of shorea species producing tengkawang, i.e. S.stenoptera,Â S.macrophylla, and S.gysbertsiana can be different from its stipulae morphology characteristic. Growth of 10 months shorea species producing tengkawang seedlings were significantly different on height and sturdiness. Seedlings height were 67,19 â 88,79 cm, seedlings diameter 9,65 â 10,33 mm and sturdiness 7 â 9,21 in range. The best seedling growth was S.stenoptera and S.macrophylla from Gunung Bunga, West Kalimantan.